Pembentukan Karakter Sopan Santun Melalui Pembiasaan di Sekolah Dasar Islam - Annisa Nidaur Rohmah; Ni’matul Asmaulla (LPPM STIT Miftahul Ulum Bangkalan, 2022)
This research is motivated by a real and worrying moral crisis. This study discusses the formation of polite character through habituation in Islamic Elementary Schools. The method used is descriptive qualitative. Based on the results of the study, in the implementation of character building through habituation, namely planning, then socialization, simulation, implementation and evaluation.